Cardiac myxoma with atypical cell population mimicking malignancy - a diagnostic pitfall - Stejskal, Vaclav; Steiner, Ivo; Vobornik, Martin (Cardiovascular pathology, 2023)
Herein, a case of a 45-year-old woman is reported with left atrial myxoma showing unique histological findings mimicking malignancy. For 3 months before surgery, the patient suffered from a long-standing fever of unknown etiology, malaise and weight loss; she had no history of malignancy. The CT scan revealed a tumorous mass in the left atrium. Grossly, the tumor had a smooth rounded surface with areas of haemorrhage on the cut surface. Microscopic examination revealed two distinct regions. One showed classical myxoma histology, the other atypical and highly cellular population with sarcoma-like or melanoma-like features mixed with inflammatory cells and posthemorrhagic changes. Immunohistochemically, the atypical cells expressed calretinin and CD31, analogous to the neighbouring bland myxoma cells. Negative markers included SOX10, S100, Melan A, HMB45, CD34, desmin, ERG, CK, LCA, CD68 and MDM2; SMARCB1/INI1 was retained. The proliferation index Ki67 was low, in about 1 % of atypical cells. The results suggest exaggerated reactive and degenerative changes of the myxoma cells rather than true malignant transformation. Similar case reports of cardiac myxomas and diagnostic challenges are discussed.
Keywords: nádory srdce; Melanoma; lidé středního věku; Heart Neoplasms; Sarcoma; melanom; srdeční síně; Myxoma; Heart Atria; sarkom; Middle Aged; Humans; lidé; ženské pohlaví; myxom; Female